Implementasi Model Project Based Learning Mata Pelajaran Geografi di Kelas X SMA Negeri 8 Luwu Timur - Syarifuddin Syarifuddin; Ramli Umar; Rosmini Maru (Universitas Negeri Makassar, 2019)
This study aims to describe the implementation of Project-Based Learning models in geography learning. The type of research is survey research. The subjects in this study were the teacher of geography, the deputy head of the curriculum, and the principal. Data collection techniques are interviews, observation, and documentation. The results showed that the form of Project-Based Learning implementation in learning geography with details: learning planning, learning implementation, and learning assessment. In learning planning is done by analyzing the contents of the 2013 curriculum content and learning design planning. Furthermore, the implementation of learning is done by determining the project, designing project completion steps, preparing project implementation schedules, completing projects, preparing reports, presenting project results, and evaluating project processes and results. Meanwhile, the assessment of learning is carried out on the aspect of attitude using observation techniques, self-assessment, and assessment between friends. Assessment of aspects of knowledge using written test techniques and assignments, as well as skills assessment using project results assessment techniques.Penelitian ini bertujuan untuk mendeskripsikan implementasi model Project-Based Learning pada pembelajaran geografi. Jenis penelitian ini adalah penelitian survei. Subjek pada penelitian ini adalah guru mata pelajaran geografi, wakil kepala bidang kurikulum, dan kepala sekolah. Teknik pengumpulan data adalah wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa bentuk implementasi Project-Based Learning pada pembelajaran geografi dengan rincian: perencanaan pembelajaran, pelaksanaan pembelajaran, dan penilaian pembelajaran. Pada perencanaan pembelajaran dilakukan dengan menganilisis standar isi kurikulum 2013 dan desain pembelajaran. Selanjutnya, pelaksanaan pembelajaran dilakukan dengan penentuan proyek, perancangan langkah-langkah penyelesaian proyek, penyusunan jadwal pelaksanaan proyek, penyelesaian proyek, penyusunan laporan, presentasi hasil proyek, dan evaluasi proses serta hasil proyek. Sementara, penilaian pembelajaran dilakukan pada aspek sikap dengan menggunakan teknik observasi, penilaian diri, dan penilaian antar teman. Penilaian pada aspek pengetahuan dengan menggunakan teknik tes tertulis dan penugasan, serta penilaian keterampilan dengan menggunakan teknik penilaian hasil proyek.